Expectativa de probabilidad teórica y de frecuencia empírica en juegos de azar - Fierro Bardají, Alfredo (1987)
Three subjects, between 8 and 11 years old, have been studied focusing on their capacity of assessing the statistical probability in random events and in their behaviour of predicting the real outcomes in these events, along a sequence of 21 experiences, repeated 3 times. The subjective statistical estimates the objective statistical probability, the empirical prediction of subjects and the real outcome of random events in preceding occasions are systematically compared. The results show that the youngest subject made his predictions on the basis of preceding outcomes more than on the basis of his estimates of probabilities, while the other older subjects made them equally on either basis. The authors also suggest the presence of individual parameters of decision under risk.